GENDER DISCRIMINATION AND WOMEN EMPLOYMENT OPPORTUNITIES IN CALABAR, CROSS RIVER STATE - NNANA OKOI OFEM; NSAN KINGSLEY TIKU (International Studies Journal)
This study was carried out to examine gender discrimination and women employment opportunities in Calabar, Cross River State. The specific objectives of the study were to: examine the relationship between educational status and women's employment opportunities in Calabar, Cross River State; access the relationship between age and women's employment opportunities in Calabar, Cross River State, and identify the relationship between marital status and women's employment opportunities in Calabar, Cross River State. Relevant literature were reviewed in line with the topic under study. The structural functionalism and feminist perspective formed the theoretical framework for this study. The study adopted survey research design where research questionnaire was used as the main instrument of data collection. The questionnaire was designed in closed ended questions and administered to the respondents. 400 questionnaires were administered and retrieved for analysis. Simple random and purposive sampling techniques were used to sample respondents for the study. Chi-square statistical tool was used to analyze hypotheses at 0.05 level of significance. After the analysis of data, the null hypotheses were rejected. The findings revealed that; there is a significant relationship between female genital mutilation and psychological development of the girl child, there is a significant relationship between educational status, age, marital status and women's employment opportunities in Calabar. Based on the findings of the study, it was recommended amongst others that: Government should provide equal opportunities in education and also within the workforce which will accelerate a woman's career. The significance of equality should start from the classroom by teaching children that gender discrimination is not right. If girls are offered equal opportunities both academically and, in their careers, they will grow up to enter the workplace assured that their talents and abilities will not be overlooked.